Impact of magnetic immobilization on the cell physiology of green unicellular algae Chlorella vulgaris - Taghizadeh, S.-M. (Taylor and Francis Inc., 2020)
Cell immobilization on the magnetic nanoparticles (MNPs) and magnetic harvesting is a novel approach for microalgal cells separation. To date, the effect of these nanoparticles on microalgal cells was only studied over a short period of time. More studies are hence needed for a better understanding of the magnetic harvesting proposes or environmental concerns relating to long-term exposure to nanoparticles. In this study, the impact of various concentrations of MNPs on the microalgal cells growth and their metabolic status was investigated over 12 days. More than 60 reduction in mitochondrial activity and pigments (chlorophyll a, chlorophyll b, and carotenoids) content occurred during the first 6 days of exposure to â¥50 Âµg/mL nanoparticles. However, more than 50 growth inhibitory effect was seen at concentrations higher than 400 Âµg/mL. Exposure to MNPs gradually induced cellular adaptation and after about 6 days of exposure to stress generating concentrations (Ë400 Âµg/mL) of IONs, microalgae could overcome the imposed damages. This work provides a better understanding regarding the environmental impact of MNPs and appropriate concentrations of these particles for future algal cells magnetic immobilization and harvesting. Â© 2020, Â© 2020 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.